2008
DOI: 10.1111/j.1471-4159.2008.05695.x
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of nigrostriatal dopamine neurotransmission by manganese is mediated by pre‐synaptic mechanism(s): implications to manganese‐induced parkinsonism

Abstract: The long-term consequences of chronic manganese (Mn) exposure on neurological health is a topic of great concern to occupationally-exposed workers and in populations exposed to moderate levels of Mn. We have performed a comprehensive assessment of Mn effects on dopamine (DA) synapse markers using Positron Emission Tomography (PET) in the non-human primate brain. Young male Cynomolgus macaques were given weekly i.v. injections of 3.3-5.0 mg Mn/kg (n=4), 5.0-6.7 mg Mn/kg (n=5), or 8.3-10.0 mg Mn/kg (n=3) for 7-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
168
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(184 citation statements)
references
References 52 publications
15
168
1
Order By: Relevance
“…Mn exposure in primates caused a marked reduction (51%) in amphetamine-induced displacement of [ 11 C]raclopride, suggesting an abnormality in presynpatic dopaminergic neurons. 20,21 These primate findings support our conclusion that chronic Mn exposure produces clinical parkinsonism through presynaptic dopamine terminal dysfunction. Determining if a similar mechanism is responsible for our human subjects' reduced striatal FDOPA uptake will require further research.…”
Section: Discussionsupporting
confidence: 80%
“…Mn exposure in primates caused a marked reduction (51%) in amphetamine-induced displacement of [ 11 C]raclopride, suggesting an abnormality in presynpatic dopaminergic neurons. 20,21 These primate findings support our conclusion that chronic Mn exposure produces clinical parkinsonism through presynaptic dopamine terminal dysfunction. Determining if a similar mechanism is responsible for our human subjects' reduced striatal FDOPA uptake will require further research.…”
Section: Discussionsupporting
confidence: 80%
“…These data suggest a direct involvement of striatal-pallidal structures in the characteristic neurological dysfunction observed in manganism. In addition, studies in Cynomolgus macaques revealed that amphetamine-induced dopamine release was inhibited in Mn-exposed animals (Guilarte et al 2008a), suggesting a direct involvement of presynaptic dopaminergic pathways.…”
Section: Disruption Of Synaptic Transmission and Glial-neuronal Commumentioning
confidence: 99%
“…Given these differences, some have suggested that Mn intoxication is associated with preservation of the nigrostriatal dopaminergic pathway, and that chronic Mn intoxication causes parkinsonism-like effects by damaging output pathways downstream of the nigrostriatal dopaminergic pathway, in areas such as the globus pallidus (Pal et al 1999), an area with propensity to accumulate high amounts of Mn. Others (Guilarte et al 2008a) indicate a decrease of dopamine release in absence of dopaminergic neuronal degeneration.…”
Section: Diagnosismentioning
confidence: 99%
“…Fluorodopa and DAT uptake values are (nearly) normal in patients with manganism (Huang et al, 2003;Kim et al, 1998;Shinotoh et al, 1997;Wolters et al, 1989), whereas uptake is markedly reduced in IPD patients. However, Guilarte et al (2008) reported that, in the non-human primate brain, chronic Mn exposure inhibited dopaminergic transmission, leading to motor deficits, in the absence of changes to presynaptic dopaminergic nerve terminals. Racette et al (2005) found relatively symmetrical and severely reduced fluorodopa uptake on PET in the posterior putamen of a patient with manganism secondary to liver failure, together with T1 hyperintensities in the basal ganglia on MRI.…”
Section: Pet/spect As An Index Of the Integrity Of The Dopaminergic Nmentioning
confidence: 99%